The Role of N-Acetyl Sistein in Pulmonary Tuberculosis - Resti Yudhawati; Nitya Prasanta (Jurnal Respirasi, 2020)
Pulmonary Tuberculosis is a chronic infection that caused by Mycobacterium tuberculosis (M.tb) infection and it is still the major health problem worldwide. Mycobacterium tuberculosis infection can induce oxidative stress. Some studies has proved that active TB patients have an association with excessive oxidative stress which causes glutathione (GSH) level decrease and free radicals increase. Glutathione (GSH) facilitates the control of M.TB intracellular bacterial growth in macrophages and has direct antimicrobial activity.  N-acetylcysteine (NAC) is thiol, a precursor of L-cysteine and glutathione synthesis (GSH) that has been used for decades as a mucolytic agent in the treatment of respiratory diseases. Some studies report beneficial role of NAC as immunomodulator, besides NAC also has anti-inflammatory and antimicrobial effect in TB management.